Implementation of Fuzzy Search and Audio Player for Web-Based Quranic Verse Retrieval - Dewi Primasari; Firman Hakim; Muhammad Danise Raditya Saneistha; Ihsan Wahid Cahya (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2025)
This study aims to develop a web-based Quranic search system integrating fuzzy search and audio player features to address typographical errors in user inputs and enhance accessibility. Employing the Prototype Development Model, we implemented the Levenshtein Distance algorithm via Fuse.js for tolerance-based text matching and integrated an interactive audio player for verse recitation. Testing with typo variations revealed optimal performance at an 80–85% similarity threshold, achieving 92% user satisfaction in handling common misspellings (e.g., "Albaqara" → "Al-Baqarah"). The system’s client-side processing ensured rapid responses (<1s), while Progressive Web App (PWA) architecture enabled offline functionality. Key contributions include: (1) a typo-resistant Quranic search interface, (2) empirical validation of threshold settings, and (3) holistic user engagement through audio-text integration. This work bridges gaps in prior studies that focused solely on exact matching or audio features, offering a novel synergy of adaptive search and multimedia interaction for Islamic digital tools.